Analysis of Total Flavonoid and Antioxidant Activity of Black Turmeric (Curcuma caesia) using ABTS (2,2-azinobis-3-Ethylbenzothiazoline-6-Sulfonic Acid) Method - Tanesib, Molesy Fransina; Indra Kurniasih, Kholif Sholehah; Nugraha, Arde Toga (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2023)
Black turmeric (Curcuma caesia) has a higher concentration of phytochemical compounds compared to other turmeric species. This means it's an incredibly potent natural antioxidant. Experts believe that black turmeric could have some amazing health benefits, such as protecting against oxidative stress and reducing inflammation. Black turmeric was extracted using the maceration method with a methanol solvent. After extracting black turmeric using the maceration method and methanol solvent, the resulting extracts were tested qualitatively for flavonoids, phenolics, and tannins. Then proceed with the quantitative test to determine the total levels of flavonoids and test the antioxidant activity using the ABTS method. The results of this study obtained a yield of 13.26%, positive qualitative test results for flavonoids, phenolics, and tannins, and total flavonoid levels of 10.326 ± 0.074 mgEQ/g extract with an IC50 of 88.581 ± 3.376 ppm. Based on the results of the antioxidant activity, black turmeric methanol extract has strong antioxidant activity.